Applicability of non-intensive innovation in the coffee, guava and raw sugar cane production in Colombia - Mesa Fandiño, Diana; Pérez Yucuna, William; Rodríguez Delgado, Andrea; Sánchez Ovalle, Vivian Ginneth (2021)
The University Corporation Minuto de Dios-UNIMINUTO- through the faculty of Business Sciences, specifically the Business Administration program in the face to face modality, has developed a macro-research project titled “ Quantification of the Multiplier Effect of the Capabilities of Soft Innovation in the Enterprise and its Effect on the Iberoamerican progress and welfare (CEMCIL)” . This project is linked to the “Management, Participation and Development – GEPADES MD” research group.